1999
DOI: 10.1080/088800199277579
|View full text |Cite
|
Sign up to set email alerts
|

Arm Anthropometry in Evaluation of Malnutrition in Children With Cancer

Abstract: Malnutrition in children with cancer is reported to be relatively uncommon at the time of diagnosis. However, in most studies nutritional status measurement has relied almost exclusively on weight-related indices. This can be misleading, because in children with malignancy, tumor masses can reach more than 10% of total body weight. A controlled study was performed in 62 patients using arm anthropometry to provide a more accurate evaluation of the nutritional status of children with cancer at presentation. Heig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 11 publications
5
41
1
3
Order By: Relevance
“…However, about 70% was identified with the use of TSFT and 54.1% with MUAC. These were in keeping with findings by Oguz et al [10] who noted no significant difference in weight related anthropometric values of children with and without cancer but showed a significant difference in the prevalence of malnutrition between the two groups when TSFT and MUAC were used to assess malnutrition in Turkish population. Also Brinksma et al [29] observed the incidence of under nutrition in newly diagnosed pediatric cancer patients to be between 23-29% using weight and height as parameters.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, about 70% was identified with the use of TSFT and 54.1% with MUAC. These were in keeping with findings by Oguz et al [10] who noted no significant difference in weight related anthropometric values of children with and without cancer but showed a significant difference in the prevalence of malnutrition between the two groups when TSFT and MUAC were used to assess malnutrition in Turkish population. Also Brinksma et al [29] observed the incidence of under nutrition in newly diagnosed pediatric cancer patients to be between 23-29% using weight and height as parameters.…”
Section: Discussionsupporting
confidence: 78%
“…However, Sala and co-workers [2] noted that weight for height (WFH) is potentially misleading in children with large abdominal tumors who can weigh over 10% of their total body weight. Oguiz et al [10] reported that arm anthropometry is a valuable means of assessing nutritional status since it is independent of tumor mass and recommended that the most essential information in evaluating nutritional status is the lean body mass. In determining the lean body mass, measurement of MUAC is essential while TSFT is important in measuring fat mass.…”
Section: Introductionmentioning
confidence: 99%
“…In the study Borazan and his friends conducted, it was detected that 50.7 % of the patients ranked in terms of malnutrition through SGA had a severe malnutrition [22,23]. It is thought that the reason why the number of the patients with malnutrition in this study was less compared with other studies was that the patients accepted to the study were chosen from the patients with no malnutrition.…”
Section: Discussioncontrasting
confidence: 39%
“…The finding that the extent of malnutrition can be significantly underestimated by weight-for-height indexes, including %IBW, is supported by the literature. In children with malignancies, measurement of skinfold thickness and midarm circumference as reference standard revealed a high prevalence of nutritional failure (Oguz et al, 1999). Yet, %IBW values of most patients remained within the normal range.…”
Section: Discussionmentioning
confidence: 99%